Unveiling the Relationship between Ceftobiprole and High-Molecular-Mass (HMM) Penicillin-Binding Proteins (PBPs) in Enterococcus faecalis - Paola Conti; Lorenzo Mattia Lazzaro; Fabio Longo; Federica Lenzo; Alessandra Giardina; Sebastiano Alberto Fortuna; Stefania Stefani; Floriana Campanile (Antibiotics, 2024)
Low-affinity PBP4, historically linked to penicillin resistance in Enterococcus faecalis, may still have affinity for novel cephalosporins. Ceftobiprole (BPR) is a common therapeutic choice, even with PBP4-related overexpression and amino acid substitution due to mutations. Our study aims to explore the interaction between BPR and High-Molecular-Mass (HMM) low-reactive PBPs in Penicillin-Resistant-Ampicillin-Susceptible/Ceftobiprole Non-Susceptible (PRAS/BPR-NS) E. faecalis clinical isolates. We conducted competition assays examining class A and B HMM PBPs from four PRAS/BPR-NS E. faecalis strains using purified membrane proteins and fluorescent penicillin (Bocillin FL), in treated and untreated conditions. Interaction strength was assessed calculating the 50% inhibitory concentration (IC50) values for ceftobiprole, by analyzing fluorescence intensity trends. Due to its low affinity, PBP4 did not display significant acylation among all strains. Moreover, both PBP1a and PBP1b showed a similar insensitivity trend. Conversely, other PBPs showed IC50 values ranging from 1/2-fold to 4-fold MICs. Upon higher BPR concentrations, increased percentages of PBP4 inhibition were observed in all strains. Our results support the hypothesis that PBP4 is necessary but not sufficient for BPR resistance, changing the paradigm for enterococcal cephalosporin resistance. We hypothesize that cooperation between class B PBP4 and at least one bifunctional class A PBP could be required to synthesize peptidoglycan and promote growth.